Involvement of cities with county rights in financing tasks pertaining to physical culture - Maja Krasucka (Economic and Environmental Studies (E&ES), 2019)
Units of local governments in Poland are responsible for running actions in the sphere of physical culture. The growing number of people practicing sports, as well as social and rearing aspects related to sports exert an influence on the activity of sports clubs and social organizations which promote physical culture. While only some sports organizations are self-sufficient economically, most of them must rely on public support. In Poland, like in the majority of European countries, one of the main sources of financing are public grants. Cities with county rights (CCRs), being a specific type of commune, undertake tasks of both communes and counties. In the sphere of tasks pertaining to physical culture this can manifest itself by higher budgetary expenses in general, including grants. Local tasks connected with sport are stiffly defined by central regulations only to an insignificant extent. Therefore it is accepted that local governments possess considerable autonomy as regards deciding about allocation of the means assigned for their realization. This concerns also the grant-based expenses. Thus, the aim of the article is to examine whether the scale of expenses borne on physical culture, including local government grants, is dependent on the size of CCRs and on the level of their financial autonomy. In this paper, the author presents differences in expenses from budgets of CCRs on tasks pertaining to physical culture (Section 926 of the budgetary classification), with particular taking account of grants which constitute them. The basic tools of descriptive statistics and study of interdependences were used. A very large spatial difference in the examined variables, both in the regional framework and within the types of communes, was found. The mean interdependence was identified between grant-based expenses and the level of financial autonomy of the cities with county rights.
Keywords: H71; L31; Z23; 330; budget; grants; local government; financing sports activity